Immigrant Assimilation and Welfare Participation: Do Immigrants Assimilate Into or Out-of Welfare - Jörgen Hansen; Magnus Lofstrom (Institute for the Study of Labor (IZA), 1999)
This paper analyzes differences in welfare utilization between immigrants and natives in Sweden using a large panel data set, LINDA, for the years 1990 to 1996. Both welfare expenditures and immigration increased in Sweden in the 1990?s. We find that immigrants use welfare to a greater extent than natives and that non-refugee immigrants utilize social assistance less than refugee immigrants. Differences in welfare participation and number of months on welfare between immigrants and natives cannot be explained by observable socioeconomic characteristics. Using a random effects probit model, we find that immigrants lower their participation rates in welfare with time spent in Sweden. Refugees display substantially higher public assistance participation rates upon arrival in Sweden compared to non-refugee immigrants, but they assimilate out-of welfare at a faster rate than non-refugee immigrants. Neither immigrant group is predicted to reach the participation rates of native households within a 20 year period in Sweden. A fixed effects logit model supports these findings. The predicted differences in the length of social assistance spells follow a very similar pattern. Simulations of the move to a national uniform benefits structure in 1998 show a decrease in the participation rate and in expenditures.
Keywords: J15; I38; I30; H53; J61; 330; Welfare; immigration; assimilation; panel data; Migranten; Flüchtlinge; Sozialhilfe; Soziale Integration; Schätzung; Schweden